Comparison Between Box-Behnken Design And Central Composite Design For Optimizing The Biosynthesis Of Silver Particles Using Curcuma Longa Extract - Thinagar, Saranya (Universiti Sains Malaysia, 2021)
Curcuma longa (C. longa) is a rhizomatous herbaceous perennial plant that belongs to the Zingiberacae, the ginger family. The most active compound found in the C. longa is curcumin that contains polyphenol which is the vital component activating the reduction process during silver nanoparticles (AgNPs) synthesis. In a biosynthesis process, optimization process is important to develop a process that results in higher yield and efficiency. The goal of this study is to determine the optimum process conditions, comparing the Box–Behnken Design (BBD) and Central-Composite Design (CCD) in optimization process and elucidating the main interacting parameters on the biosynthesis of silver particles using C. longa extract, which includes: Concentration of C. longa extract (g/L), concentration of silver nitrate (mM), temperature (°C), and time (minutes) by using response surface methodologies (RSM). Response surface models were applied by both BBD and CCD for determining optimal condition by maximizing the absorbance value. Results showed that both BBD and CCD models depicted the quadratic models with high regression coefficient of 0.9889 and 0.9448, respectively. The optimum conditions attained for BBD model are 9.53 g/L, 61.3 °C, 10.7 minutes, 1.22 mM with 1.000 desirability whereas 9.57 g/L, 60.5 °C, 10.4 minutes, 1.16 mM with 0.914 desirability based on CCD model. The BBD model generated was more reliable, with a greater prediction of absorbance value (1.100) that was very close to the actual values however the CCD model predictions were less accurate (1.078) to the actual response. The predicted response for BBD model showed excellent agreement with the actual value with residual standard error of 0.30% followed by CCD model with residual standard error of 2.52%. Consequently, it was discovered that BBD model is highly accurate, and the values associated with each optimal condition are close enough to actual results. Among the variables investigated, the concentration of C. longa extract was found to be the most significant element impacting absorbance value whereas the incubation time is least significant parameter influencing the absorbance value for both BBD and CCD model.